Unoperated tetralogy of Fallot: case report of a natural survivor who died in his 73rd year; is it ever too late to operate?. Issue 952 (8th February 2005) - Yang, X; Freeman, L J; Ross, C
Abstract : The case history is described of a man in his 73rd year who was one of the oldest surviving patients with uncorrected tetralogy of Fallot (ToF) before succumbing with renal failure. Factors contributing to his longevity included small pulmonary arteries and presumed slow development of subpulmonary obstruction together with moderate concentric left ventricular hypertrophy—features previously seen in long term survivors. Less than 3% of all patients with uncorrected ToF survive beyond their 40s but late operative repair is still a valuable option. Practicalities of renal dialysis in the presence of an intracardiac shunt are considered.